TRAINING FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) BY MAKING WALL HANGING HANDICRAFTS FOR THE COMMUNITY OF SIMPANGAN CIKARANG UTARA VILLAGE, BEKASI REGENCY - Huda, Miftakul Huda; Daspar, Daspar; Hartati, Nani; Maulana, Donny (Universitas INABA, 2023)
Micro, Small0and Medium Enterprises0(MSMEs) are the business units that have an important role in the development and growth of the Indonesian economy. With the existence of the MSME sector,0unemployment due to the labor force that is not absorbed in the world of work i0 reduced. The purpose0of this community0service is to0find out the role0of digital marketing0training services for MSME0actors in Wangun0Harja Village.0In community0service in0Wangun Harja0Village, North Cikarang0District, there are04 methods used0including observation,0interviews, training,0and counseling.0Digital marketing0plays a role in0marketing MSME0products through0digital platforms. Among0the various0existing digital0platforms, researchers0chose Instagram0ads to market0MSME products in0Wangun Harja0village, North0Cikarang District,0Bekasi Regency.0Instagram Ads0is an advertising0platform on social0media. Instagram0Ads will allow0MSMEs to create0ads on0Instagram feeds and0Instagram stories.